Appendiceal diverticulum masquerading as acute appendicitis. Issue 5 (31st May 2022) - Patel, A; Abbas, A; Bhattacharyya, R; Galaktionova, D
Abstract: Appendiceal diverticula present as rare clinical finding and are most confused with acute appendicitis. A 65-year-old female was presented to our surgical service after 1 day of right lower quadrant abdominal pain and a computed tomography evaluation, read as a diagnosis of acute appendicitis. Due to the location and quality of pain and intraoperative findings acute appendicitis was our preliminary diagnosis. Follow up with histopathology confirmed acute inflammation of an appendiceal diverticulum. With discordance in original diagnosis from final pathological evaluation, we suggest appendiceal diverticula as an important differential to consider in patients of similar clinical presentation. Surgical treatment with appendectomy and final histological diagnosis are essential in the proper treatment of this rare clinical finding.